Multivariate Padé Approximation for Solving Nonlinear Partial Differential Equations of Fractional Order. (16th March 2013) - Turut, Veyis; Güzel, Nuran
Abstract : Two tecHniques were implemented, the Adomian decomposition method (ADM) and multivariate Padé approximation (MPA), for solving nonlinear partial differential equations of fractional order. The fractional derivatives are described in Caputo sense. First, the fractional differential equation has been solved and converted to power series by Adomian decomposition method (ADM), then power series solution of fractional differential equation was put into multivariate Padé series. Finally, numerical results were compared and presented in tables and figures.